Assessment of Information Technology Governance Implementation Based on COBIT Framework 5 Focus on DSS 02 Subdomain (Deliver, Service, And Support) (Case Study of Bank XXX Branch X) - Nadya Merdeka; Gigih Forda Nama (Journal of Engineering and Scientific Research, 2021)
Abstract— Most of companies and organizations have used information technology to improve the effectiveness and efficiency of business performance. In consequence it is necessary to have good information technology governance so that the desired goals are achieved. Bank XXX Branch X always strives to provide the best, provide excellent service and work optimally. Despite using reliable information technology, when the implementation there are still some obstacles that is accumulation of service requests in the IT division of Bank XXX Branch X. In this study, an assessment of information technology governance was carried out based on the COBIT 5 framework focusing on DSS02 subdomain. Data collection methods consist of problem formulation, literature study, observation, interviews and questionnaires. The data analysis method is carried out by calculating the results of the questionnaire answers using a Likert measurement scale to get the current capability model level, expected capability model level and risk value, calculate the gap and provide recommendations for improvement. The results of this study show that the value of the current capability model in DSS02 sub domain is 4.22, the expected capability model is 4.47 and 14 recommendations for improvement are obtained.